Harmonizing Zambia’s Digital Agriculture Ecosystem: Pathways for Coordination, Uptake, and Sustainability of CGIAR-Supported Innovations - Grossi, Amanda; Amarnath, Giriraj; Dhulipala, Ram; Makungwe, Mirriam; Kasome-Pele, Winnie; Mudege, Netsayi N.; Okoth Omondi, John; Koech, Grace Jerotich; Gamoyo, Majambo Jarumani; Jacobs-Mata, Inga; Ghosh, Aniruddha (2025)
This InfoNote examines sixteen CGIAR-supported digital agriculture and climate-information innovations currently operating in Zambia and assesses how they collectively contribute to a more integrated and climate-resilient agricultural sector. The analysis identifies five major user groups—national technical agencies, extension officers, farmers, academic institutions, and multi-sectoral planners—and maps how each innovation aligns with their needs and mandates. In doing so, the InfoNote highlights complementarities and areas of duplication across tools, as well as opportunities for improved coordination, interoperability, and government uptake, particularly through Smart Zambia Institute and the education system. It also assesses alignment with national strategies and offers recommendations to strengthen harmonization and long-term sustainability.